ANALISIS KINERJA KEUANGAN DALAM MEMPREDIKSI FINANCIAL DISTRESS PADA SUB SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEKINDONESIA (BEI) - Jannah, Raudatul; Endang, Lusi; Norma, Nike; Amriani, Siti Dwi (Growth, 2023)
The research is to analyze the influence of the variables Liquidity, Profitability and Free Cash Flow on Financial Distress. The research that has been carried out has obtained less consistent results from one study to another. This research uses the banking subsector listed on the Indonesia Stock Exchange (BEI) during 2020-2022, so the research sample in this study used the purposive sampling method to produce 5 sample companies and the samples were carried out over a period of 3 years so that the sample was 15. This hypothesis testing uses multiple linear regression analysis using the SPSS application. The results show that in the analysis of the influence on Financial Distress there is an influence and no influence between other world variables, namely Liquidity and Free Cash Flow, which do not have a significant influence on Financial Distress. And one Profitability Variable has a positive and significant effect on Financial Distress. The results of testing Liquidity, Profitability and Free Cash Flow simultaneously have a positive and significant effect on Financial Distress.